Quality Evaluation of Scientific Reports Written by Higher Technology Education Alumni - Manuel Villarruel-Fuentes; Fernando Pérez-Santiago (Universidad Nacional, Costa Rica, 2015)
Current higher education in Mexico has diversified its educational approaches and professional training proposals. This has meant that degree options are varied, always concluding with the submission of a final written document structured under the guidelines required by science. Based on the above, this study involves the use of an exploratory matrix designed for the structural and content review of 193 written reports resulting from the professional practice of students who obtained their Business Administration Degrees from a Mexican technological institute. Results show that the documents did not meet the quality standards (as far as content and form) required in scientific reports; therefore, it is concluded that the level of scientific alphabetization obtained is not consistent with the indicators demanded for a high performance institution.